GEOMETRICAL SOLVING OF SOME SYSTEMS OF EQUATIONS - Markoska, Jasmina; Markoski, Gjorgji (Matematichki Bilten, 2016)
We present geometrical method for solving some systems of trigonometric, exponential, logarithmic and irrational equations. The equations are transformed and solved geometrically.